Sustainability of fall prevention exercise programmes for community-dwelling older adults: a scoping review protocol - Kathryn Sibley; D Scott Kehler; Danielle Bouchard; Ifedayo Abel-Adegbite (BMJ Open)
Introduction Falls have financial, emotional and physical implications for ageing individuals and the healthcare system. Evidence-based exercise programmes have been one of the most effective ways of preventing falls in community dwellings for older adults. However, more research is needed to understand how to sustain these programmes. This scoping review protocol describes our plan to investigate the factors influencing the sustainability of community-based fall prevention exercise programmes.Methods and analysis Our scoping review will use the Joanna Briggs Institute methodology and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews framework. The studies will have no restrictions, including publication date, language or geographic location. Key search terms concerning programme sustainability and exercise falls prevention will be conducted in Medline, EMBASE, Cumulative Index to Nursing and Allied Health Literature, Academic Search Premier, APA PsycINFO and SPORTDiscus in consultation with an experienced librarian. Once duplicates have been removed, two independent reviewers will conduct title and abstract screening, full-text screening and data extraction. Data from eligible articles will be collated and charted to summarise data into three categories: (1) study description, including publication date, author(s), study location, paper’s aim/purpose, study participants, study design and conclusion; (2) data regarding the type of exercise programme will be used using the 16-point checklist Consensus on Exercise Reporting Template; and (3) data regarding sustainability will be organised using domains from the Program Sustainability Assessment Tool. Our results will be charted through the use of Covidence to identify patterns across the studies. Additionally, narrative synthesis will be employed to articulate the study findings.Ethics and dissemination As this is a scoping review, we do not require ethics approval. We intend to share our report findings with scientists, healthcare professionals and decision-makers. We will publish our results in reputable scientific journals and present them at relevant conferences.